641 Effectiveness of onsite occupational health clinics in management of work related musculoskeletal disorders in 10, 850 information technology professionals. (24th April 2018) - Sharan, Deepak; Rajkumar, Joshua Samuel; Balakrishnan, Rajarajeshwari; Jose, Jerrish A
Abstract : Introduction: Onsite clinics play a crucial role in the provision of occupational health services. However, the effectiveness of onsite clinics in the management of work related musculoskeletal disorders (WRMSD) is an under studied area. This study reports the outcome of onsite occupational health clinics in Information Technology (IT) companies in the management of WRMSD over a 10 year period. Methods: Aprospective study was conducted from 2006 to 2016, covering 10 850 employees of IT companies in different cities in an Industrially Developing Country. The employees (6990 males and 3860 females, between the ages 20 to 60 years), were diagnosed by an experienced occupational health physician (OHP) to have a WRMSD in specific regionsfollowing extensive usage of desktop and/or laptop computer. All the employees then underwent an ergonomic workplace analysis and protocol based rehabilitation for the WRMSD by specially trained occupational physiotherapists. The employees were reviewed by the OHP monthly and at the completion of rehabilitation. Result: Most employees were software and application engineers, followed by managers and technical support staff. A total of 62% of the employees worked for at least 5–9 hours per day and 38% for 10–14 hours per day. The predominant symptoms were low back pain (for males) andneck pain (for females). Nearly, 55% were diagnosed to haveMyofascial Pain Syndrome and others with Thoracic Outlet Syndrome, Fibromyalgia, Tendinopathies and Type 1 Complex Regional Pain Syndrome. After the rehabilitation, the VAS scale showed significant reduction in pain levels (p<0.01). 78% had reported reduced productivity due to the WRMSD, which improved markedly after the rehabilitation. 93% of workers reported complete resolution of symptoms and 7% reported partial resolution of symptoms but could work without restriction. Discussion: Onsite occupational health clinics are effective in the managementof WRMSD in IT companies.